Analysis of the Implementation of the Tahfizh Program in Madrasah Aliyah - Musfiroh, Wardiyatun; Marini, Elis; Rahman, Achyar; Izati, Wilrahmi; Zuhri, M. (Al-kayyis: Journal of Islamic Education, 2024)
The development of the tahfizh program in schools has still not been completely successful in achieving targets many have failed. This research aims to analyze the implementation of the tahfizh program at the madrasah aliyah level in Indonesia. This research uses a qualitative method with a descriptive approach. Data sources were taken from twelve informants through in-depth interviews, and they were selected using the snowball sampling technique. All informants are active teachers and students at madrasah aliyah for the 2023/2024 academic year. The results of the analysis show that i) planning for the tahfizh program at madrasah aliyah, such as a learning implementation plan, exists and is made at the beginning of each semester with the K13 curriculum type. ii) the implementation of the tahfizh program at madrasah aliyah is carried out once a week with a time allocation of two hours outside structured lesson hours. iii) evaluation of the implementation of the tahfizh program is carried out at the end of each semester and is only carried out by curriculum representatives and tahfizh teachers. The results of this research can be used as initial data for future researchers in studying this problem in different contexts and issues.